Effect Of Additives On The Mechanical, Solvent Transport And Heat Ageing Properties Of Rubber Vulcanizates - Yahya, Siti Rohana (2011)

(untitled)
The influence of additives which are the ratio of accelerator to sulfur, antioxidant, and fillers on the properties natural rubber (NR) vulcanizates were investigated in this study. The mechanical and solvent transport properties of rubber vulcanizates before and after ageing for 2, 4, 6, 9, and 12 days at 100oC were carried out. Results indicated that the NR vulcanizates have better processability and mechanical properties than synthetic rubbers (SBR and EPDM). However, NR vulcanizates showed poor heat ageing and solvent resistance due to the present of highly unsaturated backbone structure.